Identification of early-maturing maize inbred lines based on multiple traits under drought and low N environments for hybrid development and population improvement - Badu-Apraku, Baffour; Akinwale, R. (Agricultural Institute of Canada, 2011)
Identification of early-maturing maize inbred lines based on multiple traits under drought and low N environments for hybrid development and population improvement. Can. J. Plant Sci. 91: 931942. Drought and low nitrogen stresses are major limiting factors to maize (Zea mays L.) production and productivity in West and Central Africa. Studies were conducted from 2007 to 2009 at three locations in Nigeria under induced drought stress and low nitrogen conditions. The objective was to identify superior inbred lines for use as parents for hybrid production and for introgression into maize breeding populations. The inbreds TZEI 17, TZEI 13, TZEI 23, TZEI 2, TZEI 3, TZEI 22, TZEI 7, TZEI 11, and TZEI 8 were identified as the most promising parents under drought stress. Under low N, TZEI 7, TZEI 11, TZEI 2, TZEI 4, TZEI 10, TZEI 8, and TZEI 22 were selected. TZEI 11, TZEI 2, TZEI 8, and TZEI 22 had combined tolerance to drought stress and low N and could be used as germplasm sources for introgression of tolerance genes as well as for the development of drought and/or low-N-tolerant hybrids. Under drought stress, TZEI 17, TZEI 3, TZEI 23, and TZEI 13 were the closest to the ideal genotype, while TZEI 7, TZEI 2, and TZEI 11 were the closest under low-N conditions.